Latin American journal of central banking (Elsevier B.V., 2020)
The Latin American Journal of Central Banking (LAJCB) publishes high-quality research on topics that are of keen interest to central banks and associated financial regulatory and supervisory agencies. The LAJCB covers traditional topics such as monetary theory and policy, exchange rates, and international finance. It also includes topics that have gained prominence more recently, such as financial stability, climate change as it relates to financial systems, financial market infrastructures and technologies.